Physicochemical and Microbiological Appearance of Sapera Goat's Milk on Frozen Storage - E. Prayitno; R. Hartanto; D.W Harjanti (Universitas Bengkulu, 2021)
This study aims to examine the effect of the storage time of milk at a temperature of -18? on the chemical, physical and microbiological content due to different storage times. The goat's milk studied was the milk of the Sannen Crossbreed of the Sapera goat. Twenty samples were taken from the milking results on the same day. The design used in this study was a completely randomized design (CRD) with five treatments and four replications. Samples were grouped according to treatment, namely 0d (control) and 10d, 20d, 30d, 40d; stored for 10, 20, 30 and 40 days, respectively. The milk storage process is carried out using a freezer at a temperature of -18?. The physicochemical and microbiological parameters observed were protein, fat, lactose, solid-non-fat (SNF), total solid (TS), specific gravity, pH, total plate count (TPC), and coliform. Evaluation of milk quality is based on the Indonesian National Standard (SNI) and Thai Agricultural Standard (TAS). The results showed that storage time did not significantly affect the components of fat, protein, lactose, total plate count, and coliform (p> 0.05). In milk stored for 40 days, there were differences in the values of SNF, TS, specific gravity, and pH compared to control (p<0.05). In terms of chemical, physical and microbiological quality, Sapera goat's milk stored at -18? for 40 days still complies with SNI and TAS. The process of storing and freezing milk can be an alternative for preservation to ensure the physical and chemical quality of Sapera goat's milk.